Management of Gingival Curettage on the Lower Anterior Teeth and Operculectomy on the Right Lower Third Molar - Dimas Cahya Aditya Saputra; Desi Sandra Sari (Health and Technology Journal (HTechJ), 2026)
Periodontitis is an advanced, destructive periodontal disease characterized by periodontal pocket formation and progressive loss of supporting tissues. Initial periodontal therapy typically involves nonsurgical approaches; however, surgical intervention may be required when clinical improvement is insufficient. This case report describes the comprehensive management of localized periodontitis stage II grade A associated with an operculum on the lower right third molar. A 35-year-old female patient presented with complaints of dental calculus on the lower anterior teeth and gingival tissue covering the lower right posterior tooth. Clinical and radiographic examinations revealed subgingival calculus, periodontal pockets measuring 3–4.5 mm, and horizontal bone resorption involving approximately one-third of the root length. Radiographic assessment also showed that the cusp of tooth 48 was positioned parallel to the occlusal line and the occlusal plane of the adjacent tooth. Initial periodontal therapy included supragingival and subgingival scaling and root planing. Operculectomy was subsequently performed on tooth 48 to remove the gingival tissue covering the crown and improve access for oral hygiene. Curettage was performed on teeth 41 and 42 to remove residual inflammatory tissue. Periodic evaluation demonstrated a reduction in gingival inflammation, with notable improvements in gingival color, consistency, and texture following curettage. Comprehensive periodontal management combining nonsurgical therapy with targeted surgical procedures such as curettage and operculectomy can effectively control inflammation and improve periodontal health. Operculectomy is particularly beneficial in cases where an operculum impedes proper cleaning of the third molar region, thereby helping to prevent recurrent inflammation and facilitate optimal periodontal maintenance.